Understanding commanders' information needs for influence operations - Larson, Eric V. (Eric Victor), 1957-; Arroyo Center; ebrary, Inc. (Santa Monica, CA : RAND, 2009)
Documents a study whose goals were to develop an understanding of commanders' information requirements for cultural and other "soft" factors in order to improve the effectiveness of combined arms operations, and to develop practical ways for commanders to integrate information and influence operations activities into combined arms planning/assessment in order to increase the usefulness to ground commanders of such operations.
"RAND Arroyo Center."
"Prepared for the United States Army."
Includes bibliographical references (p. 127-133).
Electronic reproduction.
Keywords: Generals -- United States -- Information services; Command of troops; Influence (Psychology); Information warfare -- United States; Combined operations (Military science); United States -- Armed Forces -- Planning; United States -- Armed Forces -- Officers -- Information services; United States -- Armed Forces -- Information services; United States -- Military policy; Electronic books